Assessing the potential of routine stand variables from multi-taxon data as habitat surrogates in European temperate forests. (September 2019) - Larrieu, Laurent; Gosselin, Frédéric; Archaux, Frédéric; Chevalier, Richard; Corriol, Gilles; Dauffy-Richard, Emmanuelle; Deconchat, Marc; Gosselin, Marion; Ladet, Sylvie; Savoie, Jean-Marie; Tillon, Laurent; Bouget, Christophe
Highlights: Composition of plants and saproxylic beetles assemblages co-varied with habitat variables. The contribution of habitat variables to species composition inertia was relatively weak. Forest subgroups showed weaker relationships with habitat variables than did full-taxa. We found seven habitat thresholds above which species richness was significantly higher. Abstract: To encourage forest managers to use biodiversity indicators in their work, providing environmental variables that depict species habitats, have well-calibrated and strong relationships with biodiversity and are easy to routinely record would be a step forward. The Index of Biodiversity Potential (IBP) is a rapid habitat assessment method widely used in France. It uses ten variables that indicate potential habitat for forest-dwelling species and is easy for forest managers to implement during their day-to-day activities. The objective of this paper is to evaluate the indicator power of these IBP variables at the stand scale, i.e. their capacity to co-vary with empirical species richness and composition data for nine taxa. The data were obtained from 487 plots set up in 19 forested areas in France. Taxonomic data focused on corticolous lichens, corticolous and saproxylic bryophytes, polypores, saproxylic beetles, ground beetles, hoverflies, birds, bats and vascular plants. For the latter five taxa, we built subgroups of forest-specialist species. The IBP variables were recorded on 1-ha circular plots centered on the sampling point used to record taxonomic data. We explored the relationships between the IBP variables and species composition/richness of nine taxa at the stand scale. Furthermore, we searched for threshold values for all the significant relationships found between species richness and the IBP variables. Variations in the species composition of vascular plants and saproxylic beetles, and to a lesser extent, polypores, bats and lichens, were significantly related to habitat variations (ranked according to the Procrustes significance level). The contribution of the IBP variables to the total inertia of species composition was about 18.7% on average. The IBP variables had a lower number of significant relationships with species richness than with species composition. Unexpectedly, the forest subgroups mainly showed fewer significant relationships with habitat variables than did the full-groups, both for species richness and composition. We highlighted seven significant thresholds in the habitat variables above which species richness was significantly higher. Finally, we recommend that forest managers (i) routinely use a rapid habitat assessment such as the IBP, (ii) orient silvicultural practices to ensure conservation of autochtonous tree species, large logs and different types of aquatic habitats above the thresholds highlighted in this study, and (iii) periodically complete a biodiversity assessment at the forest scale by recording taxonomic data.